An integrated machine learning and chemical space network approach for the design of potent epigenetic HDAC6 inhibitors for targeting neurological disorders - Indrasis Dasgupta; Rupchand Pandit; Vijeta Jha; Rahul Verma; Insaf Ahmed Qureshi; Sk. Abdul Amin; Shovanlal Gayen (Molecular Diversity, 2026)

Soil rejuvenation influences crop specific selective enrichment of rhizospheric microbiome - Prabhakar D. Pandit; Rajesh Pal; Rahul Warke; Hemant J. Purohit; Gangadhar M. Warke (Rhizosphere, 2026)

Pan-genome analysis of Morganella morganii reveals niche-specific selection of functional traits: friend or foe? - Rajesh Pal; Bhagyashri J. Poddar; Prabhakar D. Pandit; Hemant J. Purohit; Rahul Warke; Gangadhar M. Warke (Archives of Microbiology, 2026)

Investigating the performance of CoFe2O4@TiO2 nanomaterial as multifunctional cathode catalyst for simultaneous dye degradation and oxygen reduction in microbial desalination cell - Mohit Sahni; Rahul Kumar Mishra; Aarti Gupta; Bhim Sen Thapa; Anjali Thakur; Azmat Ali Khan; Soumya Pandit; Kuldeep Sharma; Amit Roy; Abdul Malik; Dipak A. Jadhav (Desalination, 2024)

Emergence of per- and poly-fluoroalkyl substances (PFAS) and advances in the remediation strategies - Bhim Sen Thapa; Soumya Pandit; Rahul Kumar Mishra; Sanket Joshi; Abubakr M. Idris; Tanmoy Roy Tusher (Science of The Total Environment, 2024)

Direct Numerical Simulation of a Turbulent Channel Flow with Forchheimer Drag - Soumak Bhattacharjee; Evgeny Mortikov; Andrey Debolskiy; Evgeny Kadantsev; Rahul Pandit; Timo Vesala; Ganapati Sahoo (Boundary-Layer Meteorology, 2022)

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

A novel Type I methanotroph Methylolobus aquaticus gen. nov. sp. nov. isolated from a tropical wetland - Monali C. Rahalkar; Kumal Khatri; Jyoti Mohite; Pranitha S. Pandit; Rahul A. Bahulikar (Antonie van Leeuwenhoek, 2020)

Description of ‘Ca. Methylobacter oryzae’ KRF1, a novel species from the environmentally important Methylobacter clade 2 - Kumal Khatri; Jyoti A. Mohite; Pranitha S. Pandit; Rahul Bahulikar; Monali C. Rahalkar (Antonie van Leeuwenhoek, 2020)

Polybrominated diphenyl ethers (PBDEs) in core sediments from creek ecosystem: occurrence, geochronology, and source contribution - Mahesh Tiwari; Sanjay Kumar Sahu; Rahul C. Bhangare; P. Y. Ajmal; Gauri Girish Pandit (Environmental Geochemistry and Health, 2018)

Formulation of Eco-friendly Medicated Chewing Gum to Prevent Motion Sickness - Rahul B. Shete; Vimalkumar J. Muniswamy; Ashlesha P. Pandit; Kishanchandra R. Khandelwal (AAPS PharmSciTech, 2015)